Phase transformation B1 to B2 in TiC, TiN, ZrC and ZrN under pressure - Ivashchenko, V.I.; Turchi, P.E.A.; Shevchenko, V.I. (Condensed Matter Physics, 2013)
Phase stability of various phases of MX (M=Ti, Zr; X=C, N) at equilibrium and under pressure is examined based on first-principles calculations of the electronic and phonon structures. The results reveal that all B1 (NaCl-type) MX structures undergo a phase transition to the B2-structures under high pressure in agreement with the previous total-energy calculations. The B1-MX structures are dynamically stable under very high pressure (210-570 GPa). The pressure-induced B2 (CsCl-type) MC phases are dynamically unstable even at high pressures, and TiN and ZrN are found to crystallize with the B2-structure only at pressures above 55 GPa. The first-order B1-to-B2 phase transition in these nitrides is not related to the softening of phonon modes, and the dynamical instability of B2-MX is associated with a high density of states at the Fermi level. На основi першопринципних розрахункiв електронної та фононної структур дослiджувалась стабiльнiсть рiзних фаз МХ (M = Ti, Zr; X = C, N) в рiвновазi та пiд тиском. Результати вказують на те, що всi B1 (типу NaCl) структури МХ при високому тиску зазнають фазового перетворення в B2-структури, що узгоджується з попереднiми розрахунками повної енергiї. Структури B1-MX динамiчно стабiльнi при дуже високому тиску (210÷570 ГПа). Обумовленi тиском B2 (типу CsCl) MC структури динамiчно нестабiльнi навiть при високих тисках, а TiN i ZrN кристалiзуються в B2-структурi лише при тиску вищому 55 ГПа. Фазовий перехiд першого порядку з B1 в B2 в цих нiтридах не пов’язаний iз пом’якшенням фононних мод, а динамiчна нестабiльнiсть B2-MX пов’язується з високою щiльнiстю станiв на рiвнi Фермi.